Dynamic model for the multiproduct inventory optimization with multivariate demand (2016)
Abstract: Inventory Policies for the industry are a need to its profitability and to provide adequate service to the clients. The final stage in the internal logistic of the supply chain, the storage and the final disposal, must have a correct planning, but this requires a correct management of the final products demand. New models based on Bayesian techniques are proposed in this thesis in order to do forecasts with few data and for short periods. Also, new Inventory models, and the respective optimization for a type of industry that has a storage center and final supply of its products. The work is divided in two phases. The first phase will provide a better form to forecast, and the second, the form to do optimization, to give to the industry adequate quantities to order, save, and transport to fulfill service to the clients.